4 A comprehensive assessment of the effect of recanalisation of chronic total occlusion. (24th April 2016) - Douglas, H; Johnston, NG; Hanratty, C; Harbinson, M; Walsh, SJ
Abstract : Background: Successful recanalisation of chronic total occlusion (CTO) is associated with improved mortality but a strong correlation with burden of ischaemia and symptoms is lacking. Myocardial perfusion reserve (MPR) by first-pass perfusion cardiac magnetic resonance imaging (CMR) is an accurate non-invasive measure of myocardial ischaemia. We evaluated the effect of percutaneous coronary intervention (PCI) on MPR, left ventricular ejection fraction (LVEF), angina, quality of life and six-minute walking distance (6MWD). Methods and Results: To date, 40 patients have undergone contrast-enhanced first-pass perfusion CMR, modified angina questionnaire, quality of life Short-Form 36 (SF-36) assessment and six-minute walk test before and 6 months after successful PCI. MPR was analysed by measuring the relative upslope of the signal intensity curves at stress and rest calculated for a 16 segment AHA model. MPR increased by 0.59 (95% CI, 0.32 to 0.87), p < 0.0005. LVEF improved by 1.74% (95% CI, 1.04 to 2.44), p < 0.0005 in all ventricles and by 2.84% (95% CI 0.61 to 5.06), p = 0.019 in ventricles with any degree of impairment. The number of angina episodes in a 7-day period was reduced by 1.85 (95% CI 1.36 to 2.34) p < 0.0005. SF-36 showed significant improvement in 8 subscales. The 6MWD improved by 71.48m (95% CI, 35.59 to 107.36), p < 0.0005. Conclusions: Successful recanalisation of CTO by PCI leads to a reduction in ischaemia measured by MPR, as well as an improvement in LVEF (particularly in impaired ventricles), frequency of angina, overall quality of life and 6MWD at 6 months.